Pengaruh Pemberian Minuman Probiotik terhadap Bobot Hidup, Persentase Karkas dan Income Over Feed Cost Ayam Broiler - Dara Surtina; Rica Mega Sari (Program Studi Peternakan, 2020)
This study aims to determine the effect of probiotic drinks on live weight, carcass percentage and income overfeed cost of broiler chickens. The materials used in this study were 60 DOC strains of CP 707, 311 and 511 feed andprobiotic drinks as a source of lactic acid bacteria. This study used a completely randomized design (CRD) with 5treatments and 4 replications. If F is a large treatment count from F table 5%, it means that there is a significantdifference between treatments, then the calculation is continued with the DNMRT further test. The results showed thatthe provision of probiotic drinks gave a significant difference (P <0.05) on live weight, carcass percentage and incomeover feed cost of broiler chickens. From the results of the study it can be concluded that probiotic drinks have an effecton live weight, carcass percentage and income over feed cost and the provision of 1.5 ml can help increase live weight,carcass percentage and income over feed cost.